2022
DOI: 10.1016/j.isci.2021.103664
|View full text |Cite
|
Sign up to set email alerts
|

Feto-maternal microchimerism: Memories from pregnancy

Abstract: Summary There is a bidirectional transplacental cell trafficking between mother and fetus during pregnancy in placental mammals. The presence and persistence of fetal cells in maternal tissues are known as fetal microchimerism (FMc). FMc has high multilineage potential with a great ability to differentiate and functionally integrate into maternal tissue. FMc has been found in various maternal tissues in animal models and humans. Its permanence in the maternal body up to decades after delivery sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 115 publications
(341 reference statements)
1
7
0
Order By: Relevance
“…This may reflect the increased frequency of circulating stem cells in the fetus compared to adults 58 . Human and animal studies have demonstrated that pluripotent FMc participate in the process of inflammation and wound healing 59–62 . The presence of substantial FMc in stem cells suggests a mechanism for long term maintenance of FMc which may provide a mechanism for the maintenance of pro‐ or anti‐inflammatory programing.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the increased frequency of circulating stem cells in the fetus compared to adults 58 . Human and animal studies have demonstrated that pluripotent FMc participate in the process of inflammation and wound healing 59–62 . The presence of substantial FMc in stem cells suggests a mechanism for long term maintenance of FMc which may provide a mechanism for the maintenance of pro‐ or anti‐inflammatory programing.…”
Section: Discussionmentioning
confidence: 99%
“…A hint that neoplastic adoption is not limited to transplant patients comes from the studies of fetomaternal microchimerism, a condition in which cells exchanged between a woman and her child during pregnancy persist in their bodies, sometimes for decades [194][195][196]. If the fetus is a male, fetal cells can be identified in the mother's tissues by visualizing the Y chromosome, the same approach that was used to look for cell hybrids in transplant patients.…”
Section: Are Adopted Neoplastic Cells Present In Nontransplant Patien...mentioning
confidence: 99%
“… 1 This results in the presence of maternal cells in the foetal circulation, a condition known as maternal microchimerism (MMc), as well as foetal cells in the maternal circulation, a condition known as foetal microchimerism (FMc). 2 …”
Section: Figurementioning
confidence: 99%
“…1 This results in the presence of maternal cells in the foetal circulation, a condition known as maternal microchimerism (MMc), as well as foetal cells in the maternal circulation, a condition known as foetal microchimerism (FMc). 2 In 1893, Georg Schmorl initially reported FMc, when he discovered placental trophoblast cells in women who died of eclampsia. 3 Foetal cells are now well proven to enter the maternal bloodstream throughout both human and rodent gestations.…”
mentioning
confidence: 99%